Tinjauan Fiqih Muamalah dan Fatwa DSN No:112/DSN-MUI/IX/2017 Terhadap Sewa Menyewa Lapak di Pasar Banjaran Kabupaten Bandung - Redi Hadiyanto; Muhammad Iqbal Fauzan (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Leasing at the Banjaran traditional market is a rental that should be questioned because it is accompanied by activities that are prohibited by Islamic law by renting out the stall again without the permission of the stall owner. The problem of this research is how to practice leasing in the Banjaran traditional market, how to review muamalah fiqh on renting stalls in the Banjaran traditional market using ijarah contract theory and how to review the Fatwa of the MUI National Sharia Council No. 112/DSN -MUI/2017. The purpose of this study is to find out the practice of renting stalls in the Banjaran market, reviewing the rental of stalls in the Banjaran market with muamalah fiqh, and reviewing the rental of stalls from the National Sharia Council Fatwa No. 112/DSN-MUI/2017. By obtaining data from the field and using data collection, namely interviews. The results of the study showed that there were lapak tenants who did not meet the requirements for the ijarah agreement because the lapak tenants leased back their lapak without the permission of the lapak owner. Abstrak. Sewa menyewa di pasar Banjaran merupakan sewa menyewa yang patut di pertanyakan karena di barengi oleh kegiatan yang dilarang oleh syariat islam dengan melakukan menyewakan lapaknya lagi tanpa seizin pemilik lapak. Permasalahan penelitian ini yaitu bagaimana praktik sewa menyewa di pasar Banjaran, bagaimana tinjauan fikih muamalah terhadap sewa lapak di pasar Banjaran dengan menggunakan teori akad ijarah, serta bagaimana tinjauan Fatwa Dewan Syariah Nasional MUI No 112/DSN -MUI/2017. Tujuan penelitian ini yaitu untuk mengetahui praktik sewa lapak di pasar Banjaran, meninjau sewa lapak di pasar Banjaran dengan fikih muamalah, dan meninjau sewa lapak dari Fatwa Dewan Syariah Nasional No 112/DSN-MUI/2017. Dengan memperoleh data dari lapangan dan menggunakan pengumpulan data yaitu wawancara, hasil penelitian bahwa terdapat para penyewa lapak yang tidak memenuhi syarat akad ijarah dikarenakan para penyewa lapak menyewakan kembali lapaknya tanpa seizin pemilik lapak.